"It gave me the strength and will to continue and to overcome": police officers constructing resilience while under threat from criminals. Issue 1 (3rd December 2020) - Sigad, Laura I.
Abstract : Purpose: The study aims to contribute an insider's view of how members of law enforcement and their families cope with life-threatening situations. Design/methodology/approach: The study at hand is guided by a descriptive phenomenological perspective, which is utilized to describe and analyze the experiences of five police officers living under high levels of threat from criminals. Findings: The analysis presents a multifaceted picture of the officers' experience of threat. The findings suggest that life under extreme threat is experienced by the officers as an upheaval of identity and loss of the structure of self. Yet with the aid of various individual protective factors as well as community and systemic support, the officers are able to mentally reframe this experience of vulnerability as one of personal agency. They demonstrate acceptance of the threat as part and parcel of their professional roles, a praxis of responsibility that gives them a sense of control. Emotional strain is ever-present as the reality of the threat infiltrates their personal lives and those of their families, yet the return to their core identity as protectors rather than victims allows for a reintegration of the self and is the foundation of their emerging resilience. Originality/value: This novel identity-focused model can serve as the basis for a heuristic for interpreting responses to risk and fostering resilience and as the conceptual foundation for the development of practical interventions designed to foster resilience in those exposed to critical and traumatic circumstances both inside and outside the police community.